AlliedSignal - Lobel, Sharon (Senate Hall Academic Publishing, 2005)
The AlliedSignal case demonstrates how a leader establishes an organizational culture that demands superior performance, while allowing employees to “have a life outside of work.” Two senior executives, one an avowed “workaholic” and the other a mother, who insists on making time for her family, talk about work/life balance and flexibility. They stress the importance of getting to know employees and supporting them as “whole persons.” Clear objectives, frequent communication, talented staff, and “family friendly” employer programs enhance their efforts. Employee comments from focus groups and interviews round out the executives’ perspectives The case can provoke discussion about whether the responsibilities of executives prevent them from having “work/life balance”; and whether employees truly have choice about voicing and acting upon work/life values that may be different from those of their boss. What kind of culture and leadership style do readers find attractive? Teaching notes and additional discussion questions are included.
Keywords: leadership; work/life balance; goal setting; organizational culture; human resource management; organization change management.